A METHOD TO ANALYZE THE METEOROLOGICAL RADAR ECHO OBSERVED AT SYOWA STATION, ANTARCTICA - タケヤ, ヒロシ; ハタナカ, マサヒコ; サカグチ, タケシ; ニシツジ, アキラ; ホシヤマ, ミツオ; ワダ, マコト; TAKEYA, Hiroshi; HATANAKA, Masahiko; SAKAGUCHI, Takeshi; NISHITSUJI, Akira; HOSHIYAMA, Mitsuo; WADA, Makoto (National Institute of Polar Research, 1994)
P(論文) In this paper, we propose an approach to evaluate precipitation rate from meteorological radar echo data and snow particle size distribution data. We applied our approach to analyze two sets of radar echo data which were observed at Syowa Station, Antarctica on April 6 and October 1,1988. Our evaluated precipitation rates agree with the results evaluated from the Z factor-precipitation rate relations, which were measured at Syowa Station, Antarctica. On the bases of our results, we have confidence that our approach can be applied to analyze the meteorological radar echo in Antarctica. departmental bulletin paper